Sosialisasi Pergaulan Bebas Remaja dan Dampak Hukumnya di Desa Selaawi - Rahmawati, Emma Rahmawati; Kurniasih, Nunung; Gussevi, Sofia (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2024)
This community service program provides socialization to teenagers in Selaawi Village regarding the importance of knowledge about teenage free association in the era of globalization and science and technology, which has become a highly concerning social issue. This research aims to educate teenagers about what free association is and its legal consequences, identify the factors that contribute to teenage free association, and understand the efforts made by both teenagers and parents to address this issue in the current era of globalization. The socialization program is conducted using a descriptive qualitative method, employing data collection techniques such as interviews, document analysis, observation, documentation, and drawing structured conclusions. The implementation of the activity involves delivering material and conducting question-and-answer sessions with participants. Through this socialization program, researchers seek to provide teenagers with an understanding of the legal consequences of free association and ways to prevent it within the Selaawi Village community. This initiative is expected to reduce the prevalence of inappropriate teenage social interactions and raise parental awareness of their children's social lives. Analysis results show that 97.7% of participants reported an improved understanding of teenage free association and its legal consequences after the question-and-answer session in the socialization program. These findings indicate that the program successfully enhanced teenagers' awareness of free association and its legal implications while also contributing positively to strengthening their faith in accordance with Islamic teachings.